Facilitating collaborative urban water management through university-utility cooperation. (November 2016) - Crow-Miller, Britt; Chang, Heejun; Stoker, Philip; Wentz, Elizabeth A.
Abstract: In the face of intensifying stresses such as climate change, rapid urban population growth, land use change, and public concern with rates and use restrictions, water management is becoming increasingly complex in the cities of the American West. One strategy to improve water management practices in this changing social-ecological context is to develop collaborative relationships that facilitate the engagement of multiple stakeholders at multiple scales. At the local level, one important but frequently underdeveloped collaborative link is that between university researchers and water utilities, who together occupy the interstitial space between science and decision-making, while at the same time interfacing with water users. Based on workshop data, a pilot survey, and interviews with representative water managers and university researchers from cities across the American West, we identify a number of barriers to establishing collaborative platforms from which utilities and university researchers can effectively work together to tackle challenges around sustainable urban water management in the twenty-first century. We make suggestions for overcoming these barriers and argue that developing an integrated model for university-utility collaborations is a critical area on which we must focus our collective attention if sustainable urban water management is to be achieved.